Influence Analysis Need Training To Development Competence In The Environment Government Bogor Regency - Fildzah Amzari Syahriani Tanjung; R Ira Irawati; Rusliandy Rusliandy (LPPM Universitas PGRI Sumatera Barat, 2024)
Analysis need training can influential to planning training at the end can increase performance from organization. Study This intended for analyze influence analysis need training to development competence for apparatus state civil service in the environment Government Bogor Regency. Method used is approach quantitative with Data analysis using SEM PLS on 333 samples out of a total population of 1,974 people. Research result conclude that analysis need training influential positive to development competence. If analysis need training done with OK, then planning training will appropriate target in accordance with need employee nor organization. Recommendation from study that is necessity There is repair regarding the policy of using training needs analysis which has been carried out by taking into account the time period of each training plan, and improving competency development, namely determining the appropriate training program.